Occupational therapy manual for the evaluation and range of motion and muscle strength - Proulx, Deanna; Latella, Donna (New York : Routledge, 2025)
Aimed at occupational therapy practitioners, this practical and comprehensive manual demonstrates how different assessment tools can be used to evaluate the range of motion, and strength of clients, during physical rehabilitation. The book covers the key areas of evaluation that therapists need to understand, including activity analysis, clinical observation, active range of motion, gross motor testing, goniometry, and isolated muscle testing. Reconfigured to match the clinical reasoning process, this new edition has also been reorganized by region and by joint motion to make it more user-friendly, mirroring the process by which an evaluation is conducted in practice. Also included are various appendices to support the transition to practice, as well as an "At a Glance" version of the manual itself. This is an essential manual for both occupational therapy practitioners and students in training.
1 Foundations of Practice2 Introduction and Functional Activity Observation3 Biomechanical Screening: Introduction to Active Range of Motion and Gross Muscle Testing4 Biomechanical Assessment: Introduction to Goniometry and Isolated Muscle TestingAppendices
"First edition published by Cengage Learning 2003."
Keywords: Occupational therapy; MEDICAL / Allied Health Services / Occupational Therapy